An Urban Form Experiment on Urban Heat Island Effect in High Density Area. (2016) - Hu, Youpei; White, Marcus; Ding, Wowo
Abstract: Urban heat island (UHI)effect is one of the most critical environmental issues for contemporary high-density cities. Previous studies show there is a strong co-relation between UHI and Sky View Factor (SVF), which constructs a potential linkage between UHI and urban forms. As cities grow denser and hotter, urban form manipulation strategies for mitigatingheat island become an increasingly important challenge for urban planners and designers. Taking high-density urban areas which have relatively highUHIintensity and low SVF value as the studysubject, we develop an experiment to test the possibility of mitigating UHI through optimizing SVF of urban forms. The method adopted involves the use of digital techniques such as parametric modelling, programming and optimization algorithms. The experiment evaluates and optimizes a large number of urban form samples at both coarse and fine scales and searches out the optimum urban formfor maximum or minimum SVF values under variable urban density constraints. The results of this study show that it is workable to mitigate UHI through manipulating urban form based on SVF, and indicate significantpotential for urban form optimization modelling to enlighten urban planningand design decision making concerning on UHI whilst maintaining development yields